HUBUNGAN BEBAN KERJA MENTAL DAN SHIFT KERJA TERHADAP STRES KERJA PADA PEKERJA CHECKER PT. INDOFOOD CBP SUKSES MAKMUR,TBK PALEMBANG - Laura Natalia CS; Baju Widjasena; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Work stress is a psychological hazard that occurs when a job is not in accordance with the ability, resources, and individual needs. Jobs that require special attention and work shift arrangements can be a risk factor for work stress. One of the jobs that needs special attention is the instant noodle checker. The purpose of this research is to know the relation of mental workload and work shift to work stress on checker. This study used cross sectional study using descriptive analytic method. This type of research used cross sectional study by using descriptive analytic method. Population and sampling in this study with total population,  48 workers checkers. Work stress measurements used the GHQ-12 questionnaire, and the measurement of the mental workload was subjectively measured using a NASA-TLX questionnaire. Statistic analysis in this study used Chi Square test. The results showed that there was a correlation between mental workload to work stress (p= 0.010), and there was a relation between work shift with work stress (p= 0,002). The company might install the classic music as an effort to prevent the occurrence of work stress on workers checker.